Interspecies sexual behaviour between a male Japanese macaque and female sika deer - Pelé, Marie; Bonnefoy, Alexandre; Shimada, Masaki; Sueur, Cédric (Primates, 2017)
International audience Interspecies sexual behaviour or ‘reproductiveinterference’ has been reported across a wide range ofanimal taxa. However, most of these occurrences wereobserved in phylogenetically close species and weremainly discussed in terms of their effect on fitness,hybridization and species survival. The few cases ofheterospecific mating in distant species occurred betweenanimals that were bred and maintained in captivity. Onlyone scientific study has reported this phenomenon,describing sexual harassment of king penguins by anAntarctic fur seal. This is the first article to report matingbehaviour between a male Japanese macaque (Macacafuscata yakui) and female sika deer (Cervus nipponyakushimae) on Yakushima Island, Japan. Although Japanesemacaques are known to ride deer, this individualshowed clearly sexual behaviour towards several femaledeer, some of which tried to escape whilst others acceptedthe mount. This male seems to belong to a group ofperipheral males. Although this phenomenon may beexplained as copulation learning, this is highly unlikely.The most realistic hypothesis would be that of matedeprivation, which states that males with limited access tofemales are more likely to display this behaviour. Whateverthe cause for this event may be, the observation ofhighly unusual animal behaviour may be a key to understandingthe evolution of heterospecific mating behaviourin the animal kingdom.